Comparison of superior eyelid incision and directly over the lesion incision to brow dermoid cyst excision - Kose, Rustu; Okur, M. Ihsan (Springer, 2009)
A superior eyelid incision and a directly over the lesion incision to access lateral brow dermoid cysts were compared in terms of cosmetic results, operating time, complication, recurrence, and cyst rupture. From February 2004 to March 2008, 27 patients underwent excision of lateral brow dermoid cyst lesions. Dermoid cyst excision was performed using a directly over the lesion incision in 14 patients and 13 patients via a superior eyelid incision. Both incision scars were very good in adult patients, but the aesthetic results of the superior eyelid incision were judged to be better in children. The parents were satisfied in both groups. We suggest the using of the upper eyelid crease incision in children.
Keywords: Eyelid incision; Over the lesion incision; Brow dermoid cyst